2019
DOI: 10.1093/humrep/dez042
|View full text |Cite|
|
Sign up to set email alerts
|

Sequencing of a ‘mouse azoospermia’ gene panel in azoospermic men: identification of RNF212 and STAG3 mutations as novel genetic causes of meiotic arrest

Abstract: STUDY QUESTION What is the diagnostic potential of next generation sequencing (NGS) based on a ‘mouse azoospermia’ gene panel in human non-obstructive azoospermia (NOA)? SUMMARY ANSWER The diagnostic performance of sequencing a gene panel based on genes associated with mouse azoospermia was relatively successful in idiopathic NOA patients and allowed the discovery of two novel genes involved in NOA due to meiotic arrest. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 31 publications
0
51
0
1
Order By: Relevance
“…However, it has been reported that two SNPs (rs1727130 and rs1052482) located in the 3'-UTR of the STAG3 gene were identi ed to be associated with NOA in Korean population [30]. Furthermore, homozygous or compound-heterozygous variants of the STAG3 gene have been identi ed in NOA patients from Germany, Spain, and Australia [31][32][33]. In this study, we did not identify the same variants which may be due to the small sample size and ethnic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that two SNPs (rs1727130 and rs1052482) located in the 3'-UTR of the STAG3 gene were identi ed to be associated with NOA in Korean population [30]. Furthermore, homozygous or compound-heterozygous variants of the STAG3 gene have been identi ed in NOA patients from Germany, Spain, and Australia [31][32][33]. In this study, we did not identify the same variants which may be due to the small sample size and ethnic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Animal models and genetic screening studies have confirmed genetic factors to be the common cause of spermatogenesis disorders (Cannarella, Condorelli, Duca, Vignera, & Calogero, ). For example, pathogenic variations in FANCM (Kasak et al, ), MEIOB (Gershoni et al, ), RNF212 , STAG3 (Riera‐Escamilla et al, ), TEX11 , TEX12 , TEX14 , and TEX15 (Boroujeni et al, ) genes may cause nonobstructive azoospermia in male humans. A previous study by our group also identified a male with cryptozoospermia caused by a highly pathogenic nonsense mutation in TEX15 (Wang et al, ) .…”
Section: Discussionmentioning
confidence: 99%
“…The first was the X-chromosomal gene TEX11 , 6, 26 which is, according to a current structured assessment, one of only a few genes with strong clinical validity for an association with NOA. 7 Another example is the autosomal gene STAG3 , which has only recently been described in publications by us and others in parallel, 23, 27 and its clinical validity is currently ‘moderate’. Most of the proteins involved in DNA recombination, including M1AP , are highly evolutionarily conserved.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, variants in STAG3 had previously been reported to cause POI 29 and now have recently been shown to also cause NOA and meiotic arrest. 23, 27 M1AP is predominantly expressed in the adult testis (GTEx), but also reported to be expressed in the fetal mouse ovary. 8 However, the structure of ovaries in female M1ap knockout mice appeared normal and fertility was preserved.…”
Section: Discussionmentioning
confidence: 99%